Using Multiple Case Studies to Examine the Role of Colours in SME Food Packaging - Wirania Swasty; Muhizam Mustafa (Wacana Seni Journal of Arts Discourse, 2023)
Existing studies on branding and value creation focus primarily on established brands and luxury products, with less attention paid to small and medium enterprise (SME) food souvenir products. Additionally, most studies are grounded in business, marketing, psychology, and health sciences. This study attempts to fill the gaps by enhancing understanding of the functional and emotional value of colour in food souvenir packaging from a design standpoint. Using multiple case studies, the present research intends to assess the role of colours in branding and value creation for SME food packaging in Bandung, Indonesia. The research design was comparative research. Using Microsoft Excel, the analysis was image-based descriptive and qualitative within-case and cross-case analysis based on visual perception parameters. Using common colours is advantageous for brand identification, while using uncommon colours can enhance brand visibility. In other words, common and unique colours are part of food packaging branding and value creation. The psychology of colour also influences values such as tastiness, healthiness, good quality, attractiveness, and others. This study contributes to the design literature by demonstrating that the designer may serve as a value creator in the packaging design process through colour.